Theoretical investigations on the geometric and electronic structures of polyacetylene molecule under the influence of external electric field (eXPRESS Polymer Letters, 2009)
The geometric and electronic structures of all-trans polyacetylene (PA) molecule in neutral, cationic, and anionic states have been studied theoretically by density functional theory method at the B3LYP/6-31+G* level. The results show that both the geometric and electronic structures of the PA molecule are sensitive to the external electric field (EF). For neutral PA molecule, with the increase of EF, the carbon-carbon single bonds are shortened while the carbon-carbon double bonds are elongated. The energy gap between the highest occupied molecular orbital and the lowest unoccupied molecular orbital (LUMO-HOMO gap) decreases with the EF increasing. For cationic PA molecule, the carbon-carbon single bonds and carbon-carbon double bonds on the high potential side are elongated and shortened, respectively. While, the carboncarbon single bonds and carbon-carbon double bonds on the low potential side are shortened and elongated, respectively. Contrary to the neutral PA case, the LUMO-HOMO gap increases with the EF increasing. Contrast to the case of cationic PA, the evolution of carbon-carbon bond lengths for the anionic PA molecule under the external EF reverses. The LUMO-HOMO gap of the anionic PA molecule decreases with the increase of external EF. In addition, the spatial distributions of the HOMO and LUMO under the influence of external EF are also discussed for the PA molecule in neutral, cationic, and anionic states.